Features of the development of the coordination abilities of fitness athletes aged 8-9 years - Petro Kyzim; Evgen Fedorov; Nataliya Batieieva (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the dynamics of the development of the coordination abilities of fitness athletes aged 8-9 years. Material and methods: 24 fitness athletes were tested at the beginning and at the end of the study. The following research methods were used: theoretical analysis and generalization of data from special scientific and methodological literature; pedagogical observation; pedagogical testing; methods of mathematical statistics. Results: the results of a pedagogical study of the development of the coordination abilities of fitness athletes aged 8-9 years indicate a significant increase in the indicators of coordination abilities, which confirm that the use of special complexes of exercises is an effective approach in the educational and training process. Conclusions: comparison of the dynamics of statistical indicators of the final testing of fitness athletes aged 8-9 years showed an increase in all tested indicators.